Strategies For Enhancing Consumer Interest in Server- Based Cashless Payments (E-Wallet) - Aldo Randy Barus; Joyo Winoto; Suprehatin (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: : The digital payment landscape in Indonesia demonstrates considerable potential for expansion. However, the prevalence of transactional problems often leads to consumer dissatisfaction and complaints directed toward service providers. Therefore, developing strategies to address these challenges is essential for sustaining the growth of cashless payment adoption.Purpose: This study aims  to analyze the factors influencing consumer interest in using server-based cashless payment systems (e-wallet), and to formulate strategies for enhancing this consumer interest.Design/methodology/approach: This study employed primary data collected from 358 respondents representing Generations X, Y and Z in the Jabodetabek region. The data were analyzed using Partial Least Squares-Structural Equation Modelling (PLS-SEM) and Attention, Interest, Desire, Action (AIDA) framework.Findings/Results: The results indicate that optimism and innovativeness have positive and significant effects on both perceived usefulness and perceived ease of use of e-wallets. Furthermore, perceived usefulness and perceived ease of use were found to have positive and significant effects on users’ intention to use e-wallets. Based on the AIDA model, strategies to enhance consumer interest include optimizing social media campaigns to increase engagement, implementing referral programs with incentives or rewards, and integrating gamification features to improve user retention.Conclusion: This study confirms that optimism and innovativeness significantly influence the perceived usefulness and ease of use of e-wallets, which in turn strongly affect users’ intention to adopt e-wallet services. Three key strategies to enhance consumer interest in e-wallet usage are optimizing social media campaigns, implementing referral programs, and integrating gamification mechanisms.Originality/Value (State of the Art): This study contributes to the academic literature by identifying key factors influencing digital payment adoption across Generations X, Y, and Z. Additionally, it provides practical insights for companies in addressing the specific needs of different generations in promoting digital payment adoption, particularly e-wallet services. Keywords:   fishbone, house of risk, PGA surgical suture, e-wallet, risk mitigation